NETWORK INFRASTRUCTURE FOR A UBIQUITOUS COMPUTING LEARNING ENVIRONMENT OF CEBU TECHNOLOGICAL UNIVERSITY-ARGAO CAMPUS - Benolirao, Eingilbert C (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 1, 2015, 2015)
A campus network infrastructure is a collection of interconnected Local Area Network (LAN) which includes Wireless LAN (WLAN). Hence, this study was aimed to assess the network infrastructure and the ubiquitous computing activities of the faculty and students. The qualitative and quantitative methods were used and analysed using descriptive statistics. It came up with the findings that the campus network infrastructure has internet connection with twelve Wi-Fi Access Points where computers in laboratories and offices were connected. Most of the respondents have owned their mobile computing devices and have used the internet. The faculty members have accessed the internet in the offices and considered themselves as advanced users. However, the students have accessed the internet in the classrooms and computer laboratories and considered themselves as intermediate users. The most persistent problems encountered by the users in the use of the internet were the slow internet speed and the long period of time to view/download pages as well their difficulty in finding relevant information, including the overload of information on the internet and the privacy problem. The respondents’ internet use variable is related to their internet skills. Upgrading the ISP internet bandwidth, a BYOD Program and training sessions were recommended.